Simplified EMT Model of Multiple-Active-Bridge Based Power Electronic Transformer with Integrated Energy Storage - Jianzhong Xu; Conghui Zheng; Wanying Xu; Moke Feng; Chengyong Zhao; Gen Li (CSEE Journal of Power and Energy Systems)
Due to the advanced features of multidirectional power transfer and fast smoothing of the power fluctuation in renewable energy systems, the multiple-active-bridge based power-electronic-transformer (MAB-PET) with integrated energy storage units is becoming popular. However, the accurate electromagnetic transient simulation of the MAB-PETs is extremely time-consuming due to the large number of circuit nodes and small time-step. This paper proposes a simplified EMT modeling approach for the MAB-PETs by employing the generalized state-space averaging method. First, the switching function method and Dommel algorithm are used to build the equivalent model of each power module. Further, the PET equivalent model is presented in a multi-port PM polymerization mode. The system is simplified by applying Fourier Decomposition to its state functions by ignoring high-order harmonics. Finally, a four-port equivalent voltage source circuit is obtained. The proposed simplified equivalent model is compared with the detailed model in PSCAD/EMTDC. Simulation results show the proposed approach has excellent accuracy and is 2–3 orders of magnitude faster than the DM.